Prediabetes: A Pragmatic approach to counselling and coaching - Sanjay Kalra; Arbinder Singal; Nitin Kapoor (Journal of the Pakistan Medical Association, 2022)
Prediabetes is often considered as the link between normoglycaemia and diabetes. Though a lot of emphasis is given to an individual after the development of diabetes, pre-diabetes is often not adequately addressed in clinical practice. Given a distinct diagnostic criterion, its association with metabolic complications, an opportunity to prevent further progression to diabetes and the large number of people affected with it, makes it a subject of great importance and opportunity. In this brief manuscript we compare and contrast prediabetes with diabetes mellitus. We also describe a pragmatic approach to address a patient with prediabetes. Keywords: Prediabetes, Diabetes, Diabetes Education, Counselling, Diabetes coach, Lifestyle therapy, Behavior change.